EFFECT OF AGE, AND SPLEEN AND TREATMENT STATUS ON MALE REPRODUCTIVE HORMONES AND SOME PHYSIOLOGICAL PARAMETER LEVELS IN PATIENTS WITH BETA-THALASSEMIA MAJOR - JAMELA JOUDA; RAJWAN ABDULJABBAR GHAZZAY; WAFAA F AL-MOSAWY (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This research was conducted to study the relationship between spleen status and chelation treatment status with the male reproductive hormones and some physiological parameter levels. Methods: A total of 35 males with thalassemia major (TM) patients are recruited. Patients are grouped according to (1) their age into two groups; ˂18 years and ≥18 years, (2) their spleen status into two groups; splenectomize and non-splenectomize, and (3) their chelation treatment status into two groups; regulation and irregulation. Body mass index (BMI) was calculated and blood was collected from all patients just before blood transfusion session. Hb, ABO blood groups, ferritin, and hormone (luteinizing hormone [LH], follicle-stimulating hormone [FSH], testosterone, prolactin, and cortisone) levels were determined. Results: The highest frequency of thalassemia was in Group O and the lowest was in AB. BMI was higher in TM patients aged ≥18 years, TM patients with splenectomize, and TM patient who take the treatment irregularly. TM patients aged ≥18 years have high level of LH, FSH, and testosterone. TM patients without splenectomize have higher FSH, prolactin, and testosterone. TM patients take the treatment regularly have significantly higher testosterone levels and non-significantly lower FSH level. Conclusion: The levels of cortisol and prolactin hormones are not disturbed in TM patients and not associated with the rate of transfusion, but the level of Hb and ferritin leads to underweight in BMI and may lead to endocrine dysfunction, especially sexual hormones (FSH, LH, and testosterone). These BMI and sex hormones are related to age, spleen, and treatment status.